Fluorescence-guided nodal navigation during colectomy for colorectal cancer. Issue 6 (1st August 2022) - Caprioli, Michela; Garosio, Ilenia; Botteri, Emanuele; Vettoretto, Nereo; Molteni, Beatrice; Molfino, Sarah; Yiu, Daniel; Portolani, Nazario; Baiocchi, Gian Luca
Abstract: Introduction: Indocyanine green (ICG) fluorescence is an emerging technique in the surgical field. Among its various applications, it allows surgeons to have real-time visualization of the lymphatic drainage of an organ. The primary outcome of our study is the feasibility and safety of ICG-guided colorectal surgery. Our secondary outcome is the efficacy of ICG-guided lymphadenectomy and whether or not ICG positivity correlates with the identification of nodal metastasis. Material and methods: We conducted a single-center prospective study including 32 patients who underwent surgery for colorectal cancer. For each case, ICG was injected into the tumor area either prior to or during surgery. Tumor specimens and excised lymph nodes were analyzed using hematoxylin and eosin (H&E) staining. Results: In all patients, ICG injected in the tumor area allowed clear visualization of the lymphatic drainage. A total of 499 lymph nodes were collected, with a mean of 16 per patient. Fifty ICG positive lymph nodes outside the standard lymphadenectomy zone were examined; however, none of the nodes showed signs of nodal metastasis. Conclusions: ICG-guided colorectal surgery is safe, feasible and easily reproducible, with a relatively low cost and no radiation exposure. ICG can help the surgeon to visualize the anatomical structures. We did not find an oncological diagnostic advantage in the use of ICG-guided nodal navigation.